MAGNETIC PROPERTIES OF Cu2+ SUBSTITUTED BaFe12-xCuxO19 (x= 0.1,0.2,0.3,..., 4) - Syahrul Humaidi; Ratna A S; Tua Raja S; Seri Dermayu S; Perdamean S (Department of Physics, Sebelas Maret University, 2015)
Permanent magnet Barium M-Hexaferrite, BaFe12-x Cux O19 was synthesized with a wide range of x (x = 0.1, 0.2, …, 3 and 4mole% respectively). The precursor was made by mixing BaCO3 powder and Fe2O3 powder, whereas CuO powder was used as additive. The powders were mixed together by wet milling in distilled water medium for 20 hours. The powders had been dried at a temperature of 1000C for 24 h before calcined at a temperature of 11000C for 2 hours. The powders were then grained to prepare 400 mesh (38 µm) in diameter. The samples density was determined by using Archimedes method, magnetic properties by using permagraph, crystal structure by XRD-pattern and microwave absorbing properties using VNA. The hysteresis curve showed that the value of magnetic field ranging from 43.36 G to 100.42 G , remanence magnetic induction (Br) 20G-320G, coercivity (HcJ) 1.07 kOe to 9.22 kOe and energy production (BH) max from 0.05kGOe to 0.92 kGOe with a density from 3.82 g/cm3 to 5.2 g/cm3. The effect of Cu doping tent to increase the value of density with an optimum magnetic properties at x=0.3%mole.